Denitrogenation by Adsorption of Pyridine on Ni/Support Adsorbents - Villarroel-Jorquera, M; Villarroel-Jorquera, M (Sociedad Chilena de Quimica, 2016)
In this work we have carried out the adsorption of pyridine using three different supports (activated carbon, SiO2 and γ-Al2O3). After choosing the best support, due to its higher adsorption capacity, we have impregnated the support with nickel at three different concentrations (2, 4 and 6% w/w) by wet impregnation to study the adsorption of pyridine by π-complexation. All the samples (supports and adsorbents) were characterized by N2 adsorption-desorption by the BET method and electrophoretic migration. The experimental results, for the three different supports, show that the adsorption capacity is better for γ-Al2O3, due to its higher isoelectric point. With the incorporation of nickel, no better adsorption capacities are observed, due that the nickel incorporation diminish the zero point charges of the adsorbents.